PEMBIAYAAN PENDIDIKAN BERBASIS KINERJA : Studi Kasus di SDN Rancaekek 06 Kabupaten Bandung - Helmawati; Suherman, Maman; Jamilah, Evie; Purnamasari, Aas; Ramadan, Iman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Performance-based education financing is a strategic approach to encourage improvements in the quality of education through fund allocation based on achievement of results. However, the implementation of this financing model still faces challenges in terms of planning, implementation, and reporting that are oriented towards performance. This study aims to analyze the implementation of performance-based education financing through the School Operational Assistance (BOS) Performance program at SDN Rancaekek 06, Bandung Regency. The approach used is qualitative descriptive, with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study show that SDN Rancaekek 06 received BOS Performance in the category of Schools with the Best Progress, based on a significant increase in the Education Report Card score. Funds of Rp22,500,000 were used to support priority activities such as the development of digital learning media, teacher training, diagnostic assessments, and bullying prevention programs. The planning process was carried out in a participatory and data-based manner, implementation was monitored through an internal monitoring mechanism, and reporting was submitted accountably through the ARKAS system. The implementation of performance-based financing in this school has a positive impact on increasing the capacity of the BOS team, transparency of financial management, and changes in budgeting orientation from administrative to focusing on learning outcomes. This study recommends strengthening support systems, ongoing training, and adaptive policies to encourage successful implementation of performance-based financing at the elementary school level.